2004
DOI: 10.1007/s00431-003-1363-z
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric non-neuronopathic Gaucher disease: recommendations for treatment and monitoring

Abstract: Through comprehensive and serial monitoring, ultimately, a therapeutic dose of enzyme therapy that achieves sustained benefits can be found for each child with non-neuronpathic Gaucher disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 43 publications
(40 reference statements)
2
35
0
2
Order By: Relevance
“…32 The International Collaborative Gaucher Group (ICGG) 33 has made minimum recommendations for monitoring ERTtreated and non-ERT-treated adult patients with type I disease, and similar recommendations for paediatric patients have been published. 34 Comprehensive serial monitoring of all clinically relevant aspects of the disease according to a recommended schedule is suggested. Assessments encompassed in the recommendations are physical examination, patient-reported quality of life, haemoglobin and platelet count, visceral and skeletal involvement with specified radiological techniques, and biomarkers.…”
Section: Monitoring Patients With Gaucher's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…32 The International Collaborative Gaucher Group (ICGG) 33 has made minimum recommendations for monitoring ERTtreated and non-ERT-treated adult patients with type I disease, and similar recommendations for paediatric patients have been published. 34 Comprehensive serial monitoring of all clinically relevant aspects of the disease according to a recommended schedule is suggested. Assessments encompassed in the recommendations are physical examination, patient-reported quality of life, haemoglobin and platelet count, visceral and skeletal involvement with specified radiological techniques, and biomarkers.…”
Section: Monitoring Patients With Gaucher's Diseasementioning
confidence: 99%
“…Ida and colleagues 76 presented associations between severe skeletal involvement and several patient characteristics, including treatment (ERT or BMT) and Mariani 78 and Magnaldi 105 investigated bone marrow with scintigraphy ( 99m Tc uptake) and MRI, respectively, but data pre-ERT and post-ERT were not extractable. Median follow-up 8 months 6 patients reported reduced pain intensity and frequency; n = 11 Schaison, 2002 114 Pre-ERT 14% with bone pain 6 months ERT Bone pain diminishes 1 year ERT Further reduction in bone pain; n = 108 Belmatoug, 1995 86 Follow-up 6 to 24 months Most reported a subjective reduction in bone pain; n = 26 Beutler, 1995 71 Median follow-up 26 months ERT 4/4 improved (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) a Data calculated allowing for low follow-up rates after ERT initiation. b Data calculated to allow for low follow-up rates after ERT initiation, no follow-up information for those free of crises at baseline.…”
Section: Effect Of Ert On Skeletal Involvementmentioning
confidence: 99%
“…There is some attrition of patients lost to follow-up and missing data that may not necessarily be random or recoverable. Although the Registry is not restricted to patients treated with imiglucerase, with the advent of Demographics and disease characteristics in 1,698 patients prior to treatment [8] Recommendations for initial evaluation and serial monitoring in adult patients [9,10] Phenotypic and genetic variation worldwide and in specific populations (e.g., Latin American, Asian, N370S homozygous patients) [1,[11][12][13][14][15] Estimation of life expectancy for Gaucher disease patients based largely on years alive in the pre-ERT era [16] Gaucher disease and incidence of cancer [17] Gaucher disease and increased risk for parkinsonism [ Growth and development prior to and after initiation of alglucerase/imiglucerase enzyme replacement therapy (ERT) [27] Clinical and demographic characteristics of nearly 900 children with Gaucher disease type 1 and their response to ERT [28,29] Recommendations for initial and serial monitoring in untreated and treated pediatric patients [30][31][32][33] Outcomes in pediatric patients from Latin America where previous work has shown that severity of Gaucher disease is often greater than usually encountered in the U.S. [11,12] Clinical characteristics and effectiveness of imiglucerase/alglucerase in 443 children with Gaucher disease type 1 from Latin America after 8 years of treatment [34] …”
Section: Ajh Ajhmentioning
confidence: 99%
“…На фоне адек-ватно подобранной ферментозаместительной терапии активность хитотриозидазы значительно снижается, что служит одним из важных критериев оценки эффективно-сти лечения. Контроль активности хитотриозидазы следу-ет проводить 1 раз в 4 мес [12].…”
Section: клиническая картинаunclassified